AB0686 Switched Memory B Cell Expansion is Associated with Disease Severity in Systemic Sclerosis. (9th June 2015) - Simon, D.; Bognár, A.; Balogh, P.; Németh, P.; Minier, T.; Czirják, L.; Berki, T.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterized by vascular injury, autoimmune phenomena, inflammation, and fibrosis of the skin and various internal organs. Several lines of evidence indicate that abnormal B-cell function plays a key role in the development of SSc. The anti-CD20 monoclonal antibody therapy seems to show some clinical efficacy in SSc further emphasizing the importance of B cells in the pathomechanism of the disease. The B-cell compartment in peripheral blood of SSc patients contains an elevated number of naive and a decreased number of memory B cells. Objectives: The aim of the present research was to set up an algorithm for the extended analysis of these B-cell subsets and to evaluate the clinical significance of the defined subpopulations. Methods: Peripheral blood samples were obtained from SSc patients and healthy controls, PBMCs were isolated using ficoll gradient centrifugation, followed by magnetic bead separation of CD19+ B cells. Multiparametric flow cytometry was performed with antibodies specific for CD27, IgD, CD80, CD95 molecules. Detection of CD27 and IgD was applied to distinguish between naive (CD27-IgD+) and memory (CD27+) B cells. IgD posivity was also used to separate non-switched (CD27+IgD+) and switched (CD27+IgD-) memory subsets. In addition to expression of CD80, which provides a co-stimulatory signal necessary for T cell activation and survival, expression of CD95 – FAS receptor was also examined to investigate the activation state of the previously identified B cell subpopulations. Results: The ratio of naive B cells was higher, the proportion of memory B cells, including both subsets, was decreased in SSc patients compared to healthy controls. Among SSc patients the ratio of switched memory and CD95+ memory B cells was higher in diffuse cutaneous SSc and in patients with pulmonary fibrosis. The proportion of switched memory B cells was also elevated in the anti-Scl-70 antibody positive group compared to ACA positive patients. In dcSSc patients the ratio of CD95+ memory B cells was also higher. Conclusions: According to our results detailed flow cytometric analysis of naive and memory B-cell subsets could contribute to better distinction between the two SSc subtypes and to the evaluation of disease severity, consequently may be a useful new tool in routine immunological diagnostics. Acknowledgements: This work was supported by Hungarian Scientific Research Fund - OTKA 75912 and 112939. Disclosure of Interest: None declared